Oxy-CO2 reforming of methane to syngas over CoOx/MgO/SA-5205 catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Fuel, 2006)
The OXY-CO2 methane reforming reaction (OCRM) has been investigated over CoOx supported on a MgO precoated highly macroporous silica-alumina catalyst carrier (SA-5205) at different reaction temperatures (700-900 degrees C), O-2/CH4 ratios (0.3-0.45) and space velocites (20,000-100,000cc/g/h). The reaction temperature had a profound influence on the OCRM performance over the CoO/MgO/SA-5205 catalyst; the methane conversion, CO2 conversion and H-2 selectivity increased while the H-2/CO ratio decreased markedly with increasing reaction temperature. While the O-2/CH4 ratio did not strongly affect the CH4 and CO2 conversion and H-2 selectivity, it had an intense influence on the H-2/CO ratio. The CH4 and CO2 conversion and the H-2 selectivity decreased while the H-2/CO increased with increasing space velocity. The O-2/CH4 ratio and the reaction temperature could be used to manipulate the heat of the reaction for the OCRM process. Depending on the O-2/CH4 ratio and temperature the OCRM process could be operated in a mildly exothermic, thermal neutral or mildly endothermic mode. The OCRM reaction became almost thermoneutral at an OCRM reaction temperature of 850 degrees C, O-2/CH4 ratio of 0.45 and space velocity of 46,000 cc/g/h. The CH4 conversion and H-2 selectivity over the CoO/MgO/SA-5205 catalyst corresponding to thermoneutral conditions were excellent: 95% and 97%, respectively with a H-2/CO ratio of 1.8. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: methane; oxy-CO2 reforming; Syngas